Direct targeting of Sec23a by miR-200s influences cancer cell secretome and promotes metastatic colonization - Korpal, Manav; Ell, Brian J; Buffa, Francesca M; Ibrahim, Toni; Blanco, Mario A; Celià-Terrassa, Toni; Mercatali, Laura; Khan, Zia; Goodarzi, Hani; Hua, Yuling; Wei, Yong; Hu, Guohong; et al. (Nature medicine, 2011)
The miR200 family regulates EMT through E-cadherin modulation and has been proposed to contribute to metastasis thusly. This report identifies a promoting role of miR-200 in metastatic colonization that involves a novel target, the tumor secretome. The correlation between miR-200 and metastasis in people with cancer supports the relevance of this biphasic, multifaceted role of miR-200. Although the role of miR-200s in regulating E-cadherin expression and epithelial-to-mesenchymal transition is well established, their influence on metastatic colonization remains controversial. Here we have used clinical and experimental models of breast cancer metastasis to discover a pro-metastatic role of miR-200s that goes beyond their regulation of E-cadherin and epithelial phenotype. Overexpression of miR-200s is associated with increased risk of metastasis in breast cancer and promotes metastatic colonization in mouse models, phenotypes that cannot be recapitulated by E-cadherin expression alone. Genomic and proteomic analyses revealed global shifts in gene expression upon miR-200 overexpression toward that of highly metastatic cells. miR-200s promote metastatic colonization partly through direct targeting of Sec23a, which mediates secretion of metastasis-suppressive proteins, including Igfbp4 and Tinagl1, as validated by functional and clinical correlation studies. Overall, these findings suggest a pleiotropic role of miR-200s in promoting metastatic colonization by influencing E-cadherin–dependent epithelial traits and Sec23a-mediated tumor cell secretome.